Bio‐Dem, a tool to explore the relationship between biodiversity data availability and socio‐political conditions in time and space. (15th September 2021) - Zizka, Alexander; Rydén, Oskar; Edler, Daniel; Klein, Johannes; Perrigo, Allison; Silvestro, Daniele; Jagers, Sverker C.; Lindberg, Staffan I.; Antonelli, Alexandre
Abstract: Aim: Geo‐referenced species occurrence records are a prime example of biodiversity data and a cornerstone of biodiversity research. Yet, their availability depends on non‐biological factors, including the political framework in the region of collection. Here we present Bio ‐Dem (www.bio‐dem.surge.sh ), an open‐source software to explore the relationship between the availability of species occurrence records and the political framework in countries worldwide and through time. Location: Global. Taxon: Any. Methods: Bio ‐Dem accesses the number of occurrence records available from countries worldwide from the Global Biodiversity Information Facility (www.gbif.org ) and socio‐political information from these countries from the Varieties of Democracy database (www.v‐dem.net ) as well as information on colonial history from the Issue Correlates of War Project. Results: Bio ‐Dem is available as a free graphical user interface web application at www.bio‐dem.surge.sh . Through three interactive graphs, Bio ‐Dem enables users to explore the relationship between species occurrence records and countries' regime type, freedom of movement, freedom of association, gross domestic product, education length, political corruption, armed conflict and colonial history. We describe possible links of these specific political indicators with the collection and mobilization of biodiversity data. Illustrative examples and video tutorials explaining the use of Bio ‐Dem are available at www.bio‐dem.surge.sh . Main conclusions: Bio ‐Dem provides a user‐friendly way to explore the link between socio‐political variables and the availability of species occurrence records in user‐selected taxa and geographic regions, and to generate hypotheses on their connection. We envision Bio ‐Dem as a useful tool for teachers communicating the caveats of available biodiversity data, for biodiversity scientists exploring potential spatial and temporal bias in their data, and for social scientists exploring the impact of political systems on scientific data collection and biodiversity conservation.